Mental health, eating habits and physical activity levels of elite Iranian athletes during the COVID-19 pandemic - Taheri, M.; Esmaeili, A.; Irandoust, K.; Mirmoezzi, M.; Souissi, A.; Laher, I.; Dergaa, I.; Zouhal, H. (Science & sports, 2023)
The COVID-19 pandemic has changed life styles of millions of people worldwide. This study investigated changes in the health, physical activity levels and eating habits of elite athletes during the COVID-19 pandemic lockdown in Iran. Three hundred and eighty three 383 (248 female and 135 male) elite athletes (168.82±0.07cm; 63.92±7.42kg; the body mass index (BMI): 22.3±0.78kg/m2) participated in this study. The International Physical Activity Questionnaire (IPAQ), Depression Anxiety Stress Scales (DASS-21) and the Impact of Event Scale-Revised (IES-R) study tools were used to measure levels of physical activity and mental health status, respectively. The Emotional Eater Questionnaire (EEQ) was used to assess food consumption related to emotion. Pearson and Spearman correlation analysis test were used in data analysis. Levels of depression and stress were mild and moderate, while levels of anxiety were severe and very severe in most elite athletes. There were levels of low emotional eating by elite athletes during the COVID-19 pandemic. Physical activity levels were negatively correlated with psychological mood measures (P≤0.05), while there were positive correlations between emotional eating behaviours and psychological mood measures (moderate correlation; P≤0.01) and light physical activity levels (weak correlation; P≤0.05). This study provides the first preliminary evidence showing that the COVID-19 lockdown conditions negatively influenced the eating habits and levels of physical activity and mental health in elite athletes. Regular high intensity physical activity as health strategy in elite athletes and the general population remains a strategy to improve overall health during the COVID-19 pandemic. Additionally, these findings suggest the need to devise strategies to improve the life styles of elite athletes during pandemics such as the Covid-19 pandemic. La pandémie de COVID-19 a changé les modes de vie de millions de personnes dans le monde. Cette étude a examiné certains indicateurs de bonne santé, les niveaux d’activité physique et les habitudes alimentaires d’athlètes Elite iraniens pendant le confinement lié à la pandémie de COVID-19. Trois cent quatre vingt trois (248 femmes et 135 hommes) athlètes élites (168,82±0,07cm; 63,92±7,42kg; indice de masse corporelle (IMC): 22,3±0,78kg/m2) ont participé à cette étude. Le questionnaire international sur l’activité physique (IPAQ), l’échelle DASS-21 (Depression Anxiety Stress Scales) et les scores de l’auto-questionnaire Impact of Event Scale-Revised (IES-R) ont été utilisés pour mesurer les niveaux respectifs d’activité physique et de l’état de santé mentale. L’Emotional Eater Questionnaire (EEQ) a été utilisé pour évaluer les altérations de la prise alimentaire liées à l’émotion. Le test d’analyse de corrélation de Pearson et Spearman a été utilisé pour l’analyse des données. Les niveaux de dépression et de stress étaient légers et modérés, tandis que les niveaux d’anxiété étaient sévères à très sévères chez la plupart des athlètes élites. Il y avait des niveaux de faible alimentation d’origine émotionnelle chez ces athlètes pendant la pandémie de COVID-19. Les niveaux d’activité physique étaient corrélés négativement avec les mesures de l’humeur psychologique (p≤0,05), tandis qu’il y avait des corrélations positives entre les comportements alimentaires émotionnels et les mesures de l’humeur psychologique (corrélation modérée; p≤0,01) et les niveaux d’activité physique légère (faible corrélation; p≤0,05). Cette étude apporte une preuve préliminaire que les conditions de confinement liées au COVID-19 ont influencé négativement les habitudes alimentaires et les niveaux d’activité physique et de santé mentale chez des athlètes élites. L’activité physique régulière à haute intensité aussi bien chez les athlètes élites que pour la population générale reste une stratégie pour améliorer la santé globale pendant la pandémie de COVID-19. De plus, ces résultats suggèrent la nécessité de concevoir des stratégies pour améliorer les styles de vie des athlètes élites lors de pandémies, telles que celle de Covid-19.